Relationship between laboratory method of teaching, students’ attitude and gender on students’ performance in geometry - Ajai, John Tyavbee; Ogungbile, Titilayo (Journal of Research in Instructional, 2023)
The relationship between the laboratory method of instruction, students' attitudes toward geometry, and gender on geometry performance was examined in this study. The investigation was conducted in the Jalingo metropolis of Taraba State, Nigeria. Both correlational and quasi-experimental designs were used in the investigation. The study included 160 Upper Basic School II pupils as its sample. Data were gathered using two instruments: the Geometry Achievement Test (GAT) and the Attitudes Toward Geometry Inventory (ATGI). The instruments were validated, and for the ATGI and GAT, respectively, their reliability indices were calculated to be 0.86 and 0.91. The results indicate that while student performance in geometry is inversely connected with the laboratory style of instruction, student attitudes toward geometry are positively correlated. It has been found that 56% of students' success in geometry may be predicted by factors such as their attitude toward mathematics, gender, and instructional strategies used in laboratories. According to the correlation statistics, the laboratory method accounts for 74% of student performance in geometry, gender for 9.6%, and attitude for 7.9%. To foster a good attitude toward geometry, it is recommended that the laboratory method of instruction be promoted in mathematics class.